Competencias organizacionales en la corporación Fortaleza del Valle - Jiménez Balda, María Mercedes (2021)
The development of this study aimed to determine the organizational competencies for the contribution of competitive advantage, requiring the methodological implementation in three phases, started with the characterization of the current state of the Fortaleza del Valle Corporation, through the development of an information matrix resulting from the interview model established by Murillo and Vélez (2018), where data on strategic planning, organizational hierarchy, product portfolio, and human talent are collected; Then, the second stage was developed, in which the organizational competencies were selected, forming a team of judges, applying the expert method, which allowed establishing the indicators to develop the evaluation instrument (survey), applied to the Company personnel to make the respective diagnosis after tabulation and propose an action plan. As a result of the procedure described, a total of 13 organizational competencies measured through the traffic light method were defined, concluding in the existence of 7 competencies with a high level of performance, and the remaining 6 with medium evaluations, among which are the orientation customer (89%), empowerment (89%), innovation (86%), strategic thinking (85%), integration (84%), and food safety (87%), all of which fall into an alarm level. On the other hand, with regard to the 43 established indicators, they present a high level of development 28, medium 12, and 2 low that correspond to the high degree of deficiencies in knowledge about strategic planning and the difficulties in achieving an adequate integration.